N-acetylcysteine prevents the geldanamycin cytotoxicity by forming geldanamycin-N-acetylcysteine adduct - Mlejnek, Petr; Dolezel, Petr (Chemico-biological interactions, 2014)
Geldanamycin (GDN) is a benzoquinone ansamycin antibiotic with anti-proliferative activity on tumor cells. GDN cytotoxicity has been attributed to the disruption of heat shock protein 90 (Hsp90) binding and stabilizing client proteins, and by the induction of oxidative stress with concomitant glutathione (GSH) depletion. The later mechanism of cytotoxicity can be abrogated by N-acetylcysteine (NAC). It was suggested that NAC prevents GDN cytotoxicity mainly by the restoring of glutathione (GSH) level (Clark et al., 2009). Here we argue that NAC does not protect cells from the GDN cytotoxicity by restoring the level of GSH. A detailed LC/MS/MS analysis of cell extracts indicated formation of GDN adducts with GSH. The amount of the GDN-GSH adduct is proportional to the GDN concentration and increases with incubation time. While nanomolar and low micromolar GDN concentrations induce cell death without an apparent GSH decrease, only much higher micromolar GDN concentrations cause a significant GSH decrease. Therefore, only high micromolar GDN concentrations can cause cell death which might be related to GSH depletion. Addition of NAC leads to the formation of adducts with GDN which diminish formation of GDN adducts with GSH. NAC also forms stable adducts with GDN extracellularly. Although NAC induces an increase in the GSH pool, this effect is not crucial for abrogation of GDN cytotoxicity. Indeed, the presence of NAC in the growth medium causes a rapid conversion of GDN into the GDN-NAC adduct, which is the real cause of the abrogated GDN cytotoxicity.
Keywords: Acetylcysteine; Lactams, Macrocyclic; Cell death; protinádorová antibiotika; Geldanamycin–N-acetylcysteine adduct; molekulární struktura; acetylcystein; Molecular Structure; Geldanamycin–glutathione adduct; benzochinony; Glutathione depletion; glutathion; buňky K562; K562 cells; lidé; Humans; Benzoquinones; Antibiotics, Antineoplastic; Cell Cycle; apoptóza; K562 Cells; Glutathione; buněčný cyklus; Apoptosis; makrocyklické laktamy